2017
DOI: 10.1371/journal.pone.0175940
|View full text |Cite
|
Sign up to set email alerts
|

Recombinants from the crosses between amphidiploid and cultivated peanut (Arachis hypogaea) for pest-resistance breeding programs

Abstract: Peanut is a major oilseed crop worldwide. In the Brazilian peanut production, silvering thrips and red necked peanut worm are the most threatening pests. Resistant varieties are considered an alternative to pest control. Many wild diploid Arachis species have shown resistance to these pests, and these can be used in peanut breeding by obtaining hybrid of A and B genomes and subsequent polyploidization with colchicine, resulting in an AABB amphidiploid. This amphidiploid can be crossed with cultivated peanut (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Concerning the morphological characterization of the germplasm here analyzed, our data demonstrated that the first two principal components explained a high percentage (> 80%) of the total variance, and that nine characters standout as important in the phenotypic discrimination. This is in complete accordance with previously published results using simple amphidiploids (Fávero et al, 2015;Paula et al, 2017). The fact that the hybrids were morphologically more similar to the amphidiploid progenitors than to the parent A. hypogaea (except for the hybrid IAC 503 x (A. gregoryi V 6389 x A. stenosperma V 12488) 4x ) evidenced a high percentage of wild alleles in the progenies, supporting a significant broadening of the peanut gene pool to be used for breeding.…”
Section: Discussionsupporting
confidence: 91%
“…Concerning the morphological characterization of the germplasm here analyzed, our data demonstrated that the first two principal components explained a high percentage (> 80%) of the total variance, and that nine characters standout as important in the phenotypic discrimination. This is in complete accordance with previously published results using simple amphidiploids (Fávero et al, 2015;Paula et al, 2017). The fact that the hybrids were morphologically more similar to the amphidiploid progenitors than to the parent A. hypogaea (except for the hybrid IAC 503 x (A. gregoryi V 6389 x A. stenosperma V 12488) 4x ) evidenced a high percentage of wild alleles in the progenies, supporting a significant broadening of the peanut gene pool to be used for breeding.…”
Section: Discussionsupporting
confidence: 91%
“…Peanut, as a multipurpose oilseed, is the fifth major source of plant oil worldwide [22]. The present study is pointed out that the crude oil contents of our seeds were in acceptable ranges that mentioned previously by Gulluoglu et al [4] and Ayoola et al [23].…”
Section: Discussionsupporting
confidence: 78%
“…In general, the PIs bind firmly and irreversibly to the active site of digestive enzymes and attenuate their activity, which in turn impair the protein turnover in various metabolic processes, eventually limits their growth and development (Zhu-Salzman and Zeng, 2015). Also, the resistance mediated by PIs from wild-relatives or non-host or hybrid plants is more advantageous than host-plant resistance, due to inexposure of pest midgut proteases to PIs from such plants (Parde et al, 2010;Pandey et al, 2014;Swathi et al, 2016;de Paula et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The cultivated varieties of peanut are tetraploid and known to have inadequate levels of resistance to several biotic and abiotic constraints. In contrast, the closely related wild relatives of peanut are diploid and possessed several useful disease/pest resistant traits (Holbrook and Stalker, 2003;de Paula et al, 2017). The genetic barrier of "diploid vs tetraploid" prohibited the gene flow from wild-relatives to cultivars and thereby resulted in a narrow genetic base of peanut (Stalker, 2017).…”
Section: Introductionmentioning
confidence: 99%